2011
DOI: 10.1128/jb.05309-11
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History and Functional Characterization of Three Large Genes Involved in Sporulation in Bacillus cereus Group Bacteria

Abstract: The Bacillus cereus group of bacteria is a group of closely related species that are of medical and economic relevance, including B. anthracis, B. cereus, and B. thuringiensis. Bacteria from the Bacillus cereus group encode three large, highly conserved genes of unknown function (named crdA, crdB, and crdC) that are composed of 16 to 35 copies of a repeated domain of 132 amino acids at the protein level. Bioinformatic analysis revealed that there is a phylogenetic bias in the genomic distribution of these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…In contrast, no IStron harbored a complete ORF A and a degenerated ORF B. The Bc ISt 1 variants lacking full-length copies of both ORFs were identified in five B. cereus strains (AH187, H3081.97, NC7401, BDRD-ST26 and Q1; Supplementary Table S1) that are phylogenetically closely related as they are part of a cluster of emetic strains ( 56 , 57 , 58 , 59 ) and their IStron copies are located in orthologous loci. This indicates that the ORF-less IStrons have been transmitted vertically among these strains.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no IStron harbored a complete ORF A and a degenerated ORF B. The Bc ISt 1 variants lacking full-length copies of both ORFs were identified in five B. cereus strains (AH187, H3081.97, NC7401, BDRD-ST26 and Q1; Supplementary Table S1) that are phylogenetically closely related as they are part of a cluster of emetic strains ( 56 , 57 , 58 , 59 ) and their IStron copies are located in orthologous loci. This indicates that the ORF-less IStrons have been transmitted vertically among these strains.…”
Section: Resultsmentioning
confidence: 99%
“…This conserved domain [ 51 , 52 ] ( http://www.ebi.ac.uk/interpro/entry/IPR001434 ) contains about 76 residues and is present in cell envelope proteins, often within internal repeats, of unknown function in a wide range of distantly related prokaryotes, including Archaea. Examples include three spore proteins of the Bacillus cereus group (CrdA, CrdB and CrdC) [ 53 ], a Chlamydia trachomatis major outer membrane complex protein [ 54 ] and an archaeal Methanosarcina mazei cell surface protein [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we investigated the phylogeny of the nat3 gene in the B. cereus group to whom belongs B. anthracis species (Papazisi et al , ; Reiter et al , ). To do so, we screened all the available B. cereus group genomes available (complete and draft genomes) for nucleotide sequences similar to nat3 from B. anthracis strain Sterne.…”
Section: Resultsmentioning
confidence: 99%
“…This is somewhat surprising as bacteria tend to eliminate unnecessary genes (such as an NAT enzyme with no AcCoA hydrolase or acetyltransferase activity) but can easily be accounted for ongoing evolution in the species. The phylogenetic relationship between bacilli has been a debate for decades whether they represent distinct species, but comparative genomic analyses have shown that B. anthracis has emerged as a distinct lineage within the B. cereus group through different genomic events such as gain, loss, duplication, internal deletion and lateral transfer (Papazisi et al , ; Reiter et al , ). The general locus organization around the two orthologous nat3 genes in B. cereus ATCC14579 and B. anthracis Sterne is consistent with the evolution of B. anthracis from a common B. cereus ancestor or as a lineage of B. cereus (Papazisi et al , ; Reiter et al , ) and supports our observations (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation